Like school and not like school: ambivalences in Swedish preschool teachers' enacted policy - Johan Liljestrand (Taylor & Francis Group, 2021)
There is a tension in Swedish preschool policy when it comes to a subject curriculum and a child-centred curriculum. This article examines how Swedish preschool teachers have dealt with this relationship by focusing on the purpose of the preschool and how preschool teachers become part of the enacted preschool policy. The purpose of the study is to investigate Swedish preschool teachers' policy talk pertaining to the preschool's assignment to depart from children's own interests and school-like subjects. The analysis of interviews with 10 preschool teachers shows how local policy talk is positioned in favour of a child-centred discourse, how tensions can gradually appear in the same sequence and how different actualizations in the national curriculum change the interviewees' messages. The interviews highlight how enacted preschool policy appears as multi-layered and messy, thereby actualizing a discussion about the basic purpose of the Swedish preschool and its relation to school.